2017
DOI: 10.1007/s40544-017-0149-7
|View full text |Cite
|
Sign up to set email alerts
|

Importance of surface oxide for the tribology of a Zr-based metallic glass

Abstract: Thermally grown surface oxide layers dominate the single-asperity tribological behavior of a Zr 60 Cu 30 Al 10 glass. Increase in oxidation time leads to an increased contribution of shearing and a corresponding decreased contribution of ploughing to friction. This change in the dominating friction and wear mechanism results in an overall minor decrease of the friction coefficient of oxidized surfaces compared to the metallic glass sample with native surface oxide. Our results demonstrate the importance of cre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Interestingly, there is no trace of Fe detected inside the friction track on the CuZr plate, C and O are however highly detected. Previous studies 10,38 on the exact same material showed that the oxide layer on top of the metallic glass is mostly comprised of ZrO 2 , then Cu 2 O, and a very small portion of Al 2 O 3 , that is consistent with the EDS analysis of the friction track at low load. At high load, however, Cu and C are highly detected as compared to Zr.…”
Section: Friction Tracks Morphology and Chemistrysupporting
confidence: 81%
See 2 more Smart Citations
“…Interestingly, there is no trace of Fe detected inside the friction track on the CuZr plate, C and O are however highly detected. Previous studies 10,38 on the exact same material showed that the oxide layer on top of the metallic glass is mostly comprised of ZrO 2 , then Cu 2 O, and a very small portion of Al 2 O 3 , that is consistent with the EDS analysis of the friction track at low load. At high load, however, Cu and C are highly detected as compared to Zr.…”
Section: Friction Tracks Morphology and Chemistrysupporting
confidence: 81%
“…Based on the morphology of the friction tracks, the accommodation of relative velocities is believed to be done by mixing different modes: mainly interface shearing (sliding of the ball over the patches), rolling (isolated particles), and shearing in the volume of the patches. Kang et al 10 showed that shear and ploughing were the main mechanisms contributing to friction in their case, but the shear contribution increased upon contamination time, i.e. if oxidation increased.…”
Section: Friction Tracks Morphology and Chemistrymentioning
confidence: 97%
See 1 more Smart Citation
“…On one hand, oxidation has to be avoided in many applications to prevent degradation of components [10]. On the other hand, it has been found that the oxide layer can be helpful for enhanced properties, in particular, for the strengthening of micro devices, because it can prevent the micro devices from failure upon friction [12][13][14]. Therefore, understanding the oxidation behavior of BMGs is critical and will be helpful for the control of oxidation process.…”
Section: Introductionmentioning
confidence: 99%
“…From a different perspective, thermally induced oxidation is a major chemical approach to synthesize oxide thin films for applications such as sensors, catalysts, insulators and bioimplants 29 . Oxidation of metallic glasses have also been reported to yield a ten times improvement in the wear resistance of these materials 3032 . This could be utilized by metallic glass alloys and coatings fabricated by a number of processing techniques such as laser cladding and spark plasma sintering 3335 .…”
Section: Introductionmentioning
confidence: 99%